Bilateral Teleoperation Control of a Bipedal Robot Gait Using a Manipulator. Issue 1 (2022) - Cherfouh, Koceila; Gu, Jason; Farooq, Umar; Asad, Muhammad Usman; Dey, Rajeeb; Balas, Valentina E.
Abstract: This paper discusses a new mapping algorithm for bilateral teleoperation of a bipedal robot using an Omni haptic manipulator. Researchers have previously suggested using exoskeletons to control bipedal robots remotely; however, this method's design process, maintenance, and training needed for the operator are far too complex and costly. Here, we suggest using an Omni haptic manipulator to control the walking gait of a bipedal robot and feel the left-to-right and up-and-down motion of the biped's center of mass (CM) as the robot is walking. On the master side, the Omni-Manipulator's end effector's cartesian position is scaled then mapped to the desired position for the walking gait algorithm of the biped. On the slave side, the biped robot's CM's cartesian position is mapped as the desired joint trajectory for the Omni haptic manipulator. Results were obtained through simulations in MATLAB of a 3-DoF Omni manipulator as the master robot and a 10-DoF biped robot as the slave robot.